Penerapan pembelajaran kontekstual pada materi lingkaran untuk meningkatkan kemampuan pemecahan masalah matematika - Juhana Juhana; Zuli Nuraeni; Ricki Yuliardi (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2018)
This paper presents the findings of research on the application of contextual learning on the circle material to improve the ability of problem solving math. This studi aims to determine the action of class VIII C SMP Negeri 1 Cibingbin, Kuningan regency. Research activities are carried out through lessons learned in two cycles. Based on the result of research shows that the result of student learningon the cycle 1 and the cycle 2 has experienced a significant increase. In cycle 1 the average score is 68,00 with 50 % completeness, while in cycle 2it is obtained an average of 80,31 with completeness 81,25 %. It shows an increase in average score of 12,31 an increase in learning mastery of 31,25 %. From the contextual response of the contextual learning on the circle material has made an excellent response from the students of SMP Negeri 1 Cibingbin, wich is 92,19 %. Furthermore, seen from teacher performance activity also there is improvement. If in the first Cycle the tacher’s performance earned an average score of 83,00 which is included in the criterion well, then in the second melt the average value of 92,00 which is included in the excellent category